Can the Healthy Primary School of the Future offer perspective in the ongoing obesity epidemic in young children? A Dutch quasi-experimental study - Onno C P Van Schayck; Marije Oosterhoff; Bjorn Winkens; Nina H M Bartelink; Patricia van Assema; Stef P J Kremers; Hans H C M Savelberg; Maartje Willeboordse; Maria W J Jansen (BMJ Open)
Objectives Schools play an important role in promoting healthy behaviours in children and can offer perspective in the ongoing obesity epidemic. The ‘Healthy Primary School of the Future’ (HPSF) aims to improve children’s health and well-being by enhancing school health promotion. The current study aims to assess the effect of HPSF on children’s body mass index (BMI) z-score after 1 and 2 years follow-up and to investigate whether HPSF has different effects within specific subgroups of children.Design A longitudinal quasi-experimental design.Setting Four intervention and four control schools participated; located in a low socioeconomic status region in the Netherlands.Participants 1676 children (aged 4–12 years).Interventions HPSF uses a contextual systems approach and includes health-promoting changes in the school. Central to HPSF is the provision of a daily healthy lunch and structured physical activity sessions each day. Two intervention schools implemented both changes (full HPSF), two intervention schools implemented only the physical activity change (partial HPSF).Main outcome measures BMI z-score, determined by measurements of children’s height and weight at baseline, after 1 and 2 years follow-up.Results The intervention effect was significant after 1-year follow-up in the partial HPSF (standardised effect size (ES)=−0.05), not significant in the full HPSF (ES=−0.04). After 2 years follow-up, BMI z-score had significantly decreased in children of both the full HPSF (ES=−0.08) and the partial HPSF (ES=−0.07) compared with children of the control schools, whose mean BMI z-score increased from baseline to 2 years. None of the potential effect modifiers (gender, baseline study year, socioeconomic status and baseline weight status) were significant.Conclusions HPSF was effective after 1 and 2 years follow-up in lowering children’s BMI z-scores. No specific subgroups of children could be identified who benefitted more from the intervention.Trial registration number NCT02800616.